1999
DOI: 10.1016/s0009-9236(99)80005-8
|View full text |Cite
|
Sign up to set email alerts
|

The COX-2 specific inhibitor, MK-0966, is effective in the treatment of primary dysmenorrhea

Abstract: Clinical Pharmacology & Therapeutics (1999) 65, 118–118; doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Overall, rofecoxib was significantly more effective than placebo (P < 0.009) and similar in efficacy to naproxen sodium in the evaluation of study drugs and re-medication. Similar findings were recorded in 127 patients with primary dysmenorrhoea, where mean TOPAR 8 scores were similar for both the doses of rofecoxib and of naproxen sodium (17.4, 18 and 18.4, respectively) and all were significantly better than placebo (12.5, P < 0.006) (Daniels et al 1999;M orrison et al 1999b). R ofecoxib at an init ial dose of 50 mg was similar in efficacy to naproxen sodium in the patient's overall evaluation of the study drug (mean 2.0 vs 1.9 for naproxen sodium ).…”
Section: Rofecoxibsupporting
confidence: 66%
See 3 more Smart Citations
“…Overall, rofecoxib was significantly more effective than placebo (P < 0.009) and similar in efficacy to naproxen sodium in the evaluation of study drugs and re-medication. Similar findings were recorded in 127 patients with primary dysmenorrhoea, where mean TOPAR 8 scores were similar for both the doses of rofecoxib and of naproxen sodium (17.4, 18 and 18.4, respectively) and all were significantly better than placebo (12.5, P < 0.006) (Daniels et al 1999;M orrison et al 1999b). R ofecoxib at an init ial dose of 50 mg was similar in efficacy to naproxen sodium in the patient's overall evaluation of the study drug (mean 2.0 vs 1.9 for naproxen sodium ).…”
Section: Rofecoxibsupporting
confidence: 66%
“…R ofecoxib (25 or 50 mg) and naproxen sodium (550 mg) were significantly better than placebo in providing total pain relief up to 8 h after the onset of moderate to severe pain (P µ 0.006) (Brown et al 1999b;D aniels et al 1999;M orrison et al 1999b). In one trial conducted on 63 patients, taking all the primary and secondary endpoint s like TOPAR 8, SPID 8, peak pain relief, peak PID , time to re-medication and ranking of study drugs across cycles, rofecoxib was found to be superior to placebo (P < 0.004 for all the end points except P < 0.002 for TOPAR 8) (Brown et al 1999b). Overall, rofecoxib was significantly more effective than placebo (P < 0.009) and similar in efficacy to naproxen sodium in the evaluation of study drugs and re-medication.…”
Section: Rofecoxibmentioning
confidence: 98%
See 2 more Smart Citations
“…Rofecoxib's analgesic efficacy was also evaluated in replicate studies for primary dysmenorrhea, generally accepted as a sensitive model of acute pain. Subjects with a self-reported history of moderate to severe dysmenorrhea received rofecoxib 50 mg, naproxen 550 mg, or placebo in a cross-over study over three menstrual cycles (Brown et al, 1999b). Both rofecoxib and naproxen produced greater analgesia over 8 hrs as assessed by pain relief and pain intensity difference scores, time to onset of pain relief, and percent of patients requiring additional analgesic over the first 12 hrs.…”
Section: (Vi) Cox-2 Inhibitorsmentioning
confidence: 99%